Impaired muscle function in a mouse surgical model of post-traumatic osteoarthritis. Issue 6 (June 2016) - van der Poel, C.; Levinger, P.; Tonkin, B.A.; Levinger, I.; Walsh, N.C.
Summary: Objectives: Using a mouse surgical model of post-traumatic osteoarthritis (OA), we sought to determine if muscle function is altered following acute joint injury and whether this relates to OA progression. Design: Male C57BL/6 mice underwent surgical transection of the medio-meniscal tibial ligament destabilisation of the medial meniscus (DMM) or sham surgery on one knee. Tibialis anterior (TA) muscle function was assessed in situ at 1, 4 and 8 weeks post-surgery. Cartilage damage and joint inflammation were assessed by histologic scoring. Muscle mRNA expression was quantified by qRT-PCR. Results: Tetanic and twitch force production between DMM and sham muscle did not differ at 1 week post-surgery. Muscle function improved in both groups with time, but specific force production in DMM muscles was 18% and 22% lower than sham muscles at 4 and 8 weeks post-surgery respectively. At 8 weeks post-surgery, DMM muscles had a 40% slower relaxation rate and reduced expression of sarcoplasmic/endoplasmic reticulum Ca 2+ ATPase (Serca) pump mRNA compared to sham muscles; both observations indicate likely alterations in muscle Ca 2+ handling. There were no histologic signs of muscle atrophy or inflammation in DMM TA muscles. Specific force production in both sham and DMM mice showed a negative correlation with the severity of joint inflammation. Conclusions: Acute knee injury in the DMM model of post-traumatic OA leads to a persistent deficit in TA muscle function that occurs in the absence of muscle atrophy. This study highlights that the impact of acute knee injury is unlikely to be limited to the muscles controlling knee movement.